2002
DOI: 10.1161/hc0502.103348
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell–Mediated Lysis of Endothelial Cells in Acute Coronary Syndromes

Abstract: Background-CD4 T lymphocytes accumulate in unstable plaque. The direct and indirect involvement of these T cells in tissue injury and plaque instability is not understood. Methods and Results-Gene profiling identified perforin, CD161, and members of the killer-cell immunoglobulin-like receptors as being differentially expressed in CD4 ϩ CD28 null T cells, a T-cell subset that preferentially infiltrates unstable plaque. Frequencies of CD161 ϩ and perforin-expressing CD4 T cells in peripheral blood were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
271
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 337 publications
(287 citation statements)
references
References 38 publications
8
271
0
8
Order By: Relevance
“…Such T cells have altered tissue trafficking (45), are biased toward proinflammatory action, and preferentially interact with mesenchymal cells, such as synovial fibroblasts, in peripheral tissues (46). Senescent CD4 T cells accumulate in unstable atherosclerotic plaques and have been implicated in plaque destabilization, providing a link to the increased cardiovascular risk in RA patients (47)(48)(49). Premature senescence of the RA immune system is not limited to the memory T cell pool; it also involves naive T cells (43), the reserve pool of T cells that protect from infection and malignancy and enable tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Such T cells have altered tissue trafficking (45), are biased toward proinflammatory action, and preferentially interact with mesenchymal cells, such as synovial fibroblasts, in peripheral tissues (46). Senescent CD4 T cells accumulate in unstable atherosclerotic plaques and have been implicated in plaque destabilization, providing a link to the increased cardiovascular risk in RA patients (47)(48)(49). Premature senescence of the RA immune system is not limited to the memory T cell pool; it also involves naive T cells (43), the reserve pool of T cells that protect from infection and malignancy and enable tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, Nakajima et al (33) have recently shown that a subset of CD4ϩ T cells that are abundant in patients with atherosclerosis express perforin and that these are potent mediators of granule-mediated apoptosis of endothelial cells. The expression of perforin by this subset of T cells is strongly correlated with unstable angina, suggesting a key role for the granzyme/perforin pathway in acute coronary syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD28– T cells were shown to produce the cytotoxic molecules perforin and granzyme B, which resulted in cytolysis of the endothelium in vitro 29, 30. CD4+CD28– T cells have been found in patients with cerebrovascular and cardiovascular diseases such as acute coronary syndrome27, 31 and stroke 32, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…In the CD137‐deficient atherosclerotic vessels of ApoE − / − CD137 − / − mice, crosslinking CD137L activation with soluble CD137 protein ex vivo activated CD137L signaling and led to the release of proinflammatory cytokines, such as TNF‐α and monocyte chemotactic protein‐1 (MCP‐1) 11. In ACS patients, blocking the CD137 pathway in vitro remarkably reduced the production of TNF‐α and IFN‐γ from circulating CD4+CD28– T cells, which were reported to induce rupture of atherosclerotic plaques by direct cytolysis of arterial smooth muscle and endothelial cells 27, 30. In our serial study, despite an irregular change of lymphocyte counts in the stroke patients, CD137 expression in the CD4+ and CD4+CD28– T cells displayed a decreasing trend at 3 and 14 days posttreatment with statin, a well‐known cholesterol‐lowering drug with multiple antiinflammatory properties 36.…”
Section: Discussionmentioning
confidence: 99%